2013
DOI: 10.1158/1535-7163.targ-13-a276
|View full text |Cite
|
Sign up to set email alerts
|

Abstract A276: Phase 1 multicenter, open label, dose-escalation study of LEE011, an oral inhibitor of cyclin-dependent kinase 4/6, in patients with advanced solid tumors or lymphomas.

Abstract: Background: LEE011 is an oral small molecule inhibitor with highly specific nanomolar inhibitory activity against CDK4/cyclinD1 and CDK6/cylinD3 complexes. Preclinical studies with LEE011 have demonstrated robust anti-tumor activity in several tumor models with functional retinoblastoma protein (pRb). Methods: The primary objective this phase 1 dose escalation study was to determine the maximum tolerated dose (MTD) based on cycle 1 dose-limiting toxicities (DLTs) and establish the recommended do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…Because abemaciclib inhibits renal effl ux transporters [multidrug and toxin extrusion (MATE) 1 and 2-K] that mediate active secretion of creatinine from the proximal tubule, increases in serum creatinine during therapy with abemaciclib may not accurately refl ect renal function, and measures of glomerular fi ltration rate that are independent of active tubular secretion via renal effl ux transporters (such as cystatin C) may yield a more accurate estimate of renal function than serum creatinine for patients receiving the drug. Previous reports have identifi ed neutropenia as an adverse event associated with dual inhibition of CDK4 and CDK6 (34)(35)(36)(37)(38)(39) as a single agent on a continuous schedule in the tumor-specifi c cohorts was associated with an acceptable incidence of investigator-reported grade 3 (9%, 16 of 173 patients) or grade 4 (1%, 2 of 173 patients) neutropenia. Febrile neutropenia was rare, occurring in only 1 patient over the entire study.…”
Section: Discussionmentioning
confidence: 99%
“…Because abemaciclib inhibits renal effl ux transporters [multidrug and toxin extrusion (MATE) 1 and 2-K] that mediate active secretion of creatinine from the proximal tubule, increases in serum creatinine during therapy with abemaciclib may not accurately refl ect renal function, and measures of glomerular fi ltration rate that are independent of active tubular secretion via renal effl ux transporters (such as cystatin C) may yield a more accurate estimate of renal function than serum creatinine for patients receiving the drug. Previous reports have identifi ed neutropenia as an adverse event associated with dual inhibition of CDK4 and CDK6 (34)(35)(36)(37)(38)(39) as a single agent on a continuous schedule in the tumor-specifi c cohorts was associated with an acceptable incidence of investigator-reported grade 3 (9%, 16 of 173 patients) or grade 4 (1%, 2 of 173 patients) neutropenia. Febrile neutropenia was rare, occurring in only 1 patient over the entire study.…”
Section: Discussionmentioning
confidence: 99%
“…Results for 78 patients treated on the phase I study of LEE011 have been reported (26). Both intermittent and continuous doses were evaluated with recommended phase II doses of 600 mg daily (continuous) and 900 mg daily for 3 weeks of 4.…”
Section: Clinical-translational Advancesmentioning
confidence: 99%
“…S1; refs. 25,27). To demonstrate its impact on tumor cells in vitro, we examined the effects of LEE011 in liposarcoma cells.…”
Section: Cdk4 Knockdown Inhibits Rb Phosphorylation and Cell Growth Imentioning
confidence: 99%